Comprehensive Bonding Analysis of Tetravalent f-Element Complexes of the Type [M(salen)2] - Kloditz, Roger; Radoske, Thomas; Schmidt, Moritz; Heine, Thomas; Stumpf, Thorsten; Patzschke, Michael (Inorganic Chemistry, 2021)
Key questions for the study of chemical bonding in actinide compounds are the degree of covalency that can be realized in the bonds to different donor atoms and the relative participation of 5f and 6d orbitals. A manifold of theoretical approaches is available to address these questions, but hitherto no comprehensive assessments are available. Here, we present an in-depth analysis of the metal-ligand bond in a series of actinide metal-organic compounds of the [M(salen)2] type (M = Ce, Th, Pa, U, Np, Pu) with the Schiff base N,N′-bis(salicylidene)ethylenediamine (salen). All compounds except the Pa complex (only included in the calculations) have been synthesized and characterized experimentally. The experimental data are then used as a basis to quantify the covalency of bonds to both N- and O-donor atoms using simple electron-density differences and the quantum theory of atoms in molecules (QTAIM) with interacting quantum atoms. In addition, the orbital origin of any covalent contributions was studied via natural population analysis (NPA). The results clearly show that the bond to the hard, charged O-donor atoms of salen is consistently not only stronger but also more covalent than bonds to the softer N-donor atoms. On the other hand, in a comparison of the metals, Th shows the most ionic bond character even compared to its 4f analogue Ce. A maximum of the covalency is found for Pa or Np by their absolute and relative covalent bond energies, respectively. This trend also correlates with a significant f- and d-orbital occupation for Pa and Np. These results underline that only a comprehensive computational approach is capable of fully characterizing the covalency in actinide complexes.
CRIS-Team Scopus Importer:2022-04-14